Integrated E-Commerce Inventory Information System Application to Support Halal Traceability in Wet Noodle SMEs - Aditia Ginantaka; Aisah Rini Susanti (ABDISAINS, 2025)
Wet noodle products are a type of product that has a high halal critical point due to the complex production process and raw materials. A raw material inventory information system is needed to support more systematic raw material data collection. This service uses Halal Food Trust software to apply a raw material inventory information system. The system uses Microsoft Visual basic programming with consideration of the objectives of system development, where the scope of the data management system is integrated with the Windows operating system and Microsoft Office, which has been used routinely by SMEs. The results of the identification of the current condition of UKM Mie have carried out the management of raw material inventory; there are activities of recording raw materials at the time of purchase, storage, and use of materials in the production process carried out using a log book using Microsoft Excel. The Halal Food Trust, material inventory information system, seeks to increase the level of traceability at a high level with criteria, namely the ability to document electronically and be able to provide documents that can be printed.